Image-text guided fundus vessel segmentation via attention mechanism and gated residual learning - Xu, Jianguo; Liu, Qingyou; Shen, Jianxin; Tan, Rong; Tian, Sukun; Chi, Wei; Yang, Weihua (Frontiers in Cell and Developmental Biology, 2025)
BackgroundFundus vessel segmentation is crucial for the early diagnosis of ocular diseases. However, existing deep learning-based methods, although effective for detecting coarse vessels, still face challenges in segmenting fine vessels and heavily rely on time-consuming and labor-intensive pixel-level annotations.MethodsTo alleviate these limitations, this study proposes an image-text guided segmentation model enhanced with the Squeeze-and-Excitation (SE) module and gated residual learning. Concretely, the multimodal fundus vessel datasets with text labels are primarily constructed, effectively supporting our pioneering effort to successfully introduce an image-text model into fundus vessel segmentation. Secondly, an improved image-text model is meticulously designed, focusing on the following two aspects: (1) embedding the SE module in the CNN backbone to adaptively recalibrate channel weights for enhanced vessel feature representation; (2) integrating gated residual learning into the ViT backbone to dynamically regulate the information flow between image and text features.ResultsExtensive quantitative and qualitative experiments on two publicly available datasets, including DRIVE and ROSE-1, demonstrate that the proposed model achieves superior segmentation performance. Specifically, on the DRIVE dataset, the model attains an F1-score of 82.01%, an accuracy of 95.72%, a sensitivity of 83.25%, and a specificity of 97.43%. On the ROSE-1 dataset, the model records an F1-score of 86.34%, an accuracy of 94.61%, a sensitivity of 90.14%, and a specificity of 95.80%. Compared with most deep learning methods, these results reveal the competitiveness of the improved model, indicating its feasibility and potential value in fundus vessel segmentation, which is expected to expand a new research approach in this field.